La paisajización de la mujer en Agustín Lara - Fonseca González, Vanessa (CIICLA, Universidad de Costa Rica, 2019)
This article explores how Agustín Lara, the famous Mexican poet and composer, sings to women using rhetorical strategies such as metaphors, sinestesias, and metonymies that result in a sort of landscaspe representing her body. This methodological strategy results from a multidisciplinary approach to Lara’s texts: on one hand, as literary texts, on another hand as spaces where different traditions on love discourse converge. This aesthetic landscaping of the female body goes hand in hand with several “moral experiments”, where the lover subsumes into sensual laberynths, where love rituals take place as sacrifices or symbolic death.